First principles calculations of hyperfine magnetic field in RECd compounds (RE=Ce,Gd and Er) using FP-LAPW ELK code - Maciel, Levy Scalise (2020)
The use of nuclear techniques, mainly Time Differential Perturbed Angular Correlation Spectroscopy (PAC), for the study of materials provides information on the interactions between the energy levels of an atomic nucleus with the electrmagnetic fields surrounding this nucleus, and this type of phenomenon is called Hyperfine Interactions (HI). The information on these interactions is contained in various hyperfine quantities, among which the most important are the Electric Field Gradient (EFG) and the Magnetic Hyperfine Field (MHF). Given the gigantic scientific capacity of electronic structure calculations based on Density Functional Theory (DFT), they are a great tool for the investigation of HIs either as a purely theoretical study or as an addition to experimental measurements. This work implies calculating the hyperfine magnetic field in the RECd compounds (RE = Ce, Pr, Gd, Nd, Sm, Tb, Dy, Ho, Er, Eu, Tm and Yb) with first principles methods based on the density functional theory using the FP-LAPW ELK code and comparing the outcome to the experimental results, as well as to those obtained with the WIEN2k code. To achieve this goal, calculations were carried out for the RECd compounds. Firstly, the parameters needed to apply the calculation methodology were optimized, then the calculations were carried out by varying the polarization of spins for each compound in order to investigate their impact on MHF. After that, the MHF and the density of states (DOS) of all compounds in their various spin polarization configurations were calculated, so that a more thorough analysis of the results became possible. The work concludes with four appendices, the first is an explanation of the Born- Oppenheimer Approximation used to treat many-body systems, the second contains the proofs of the two main theorems of the DFT, the Hohenberg-Kohn Theorems, the third is a step-by-step tutorial on how to start a calculation with the ELK and the fourth comprises the optimization graphs which haven\'t got into the main text.